An examination of electronic nicotine delivery system use among college students using social cognitive theory. Issue 6 (24th August 2022) - Greer, Anna E.; Morgan, Kerry; Samuolis, Jessica; Diaz, Gabrielle; Merighi, Julianna; Mahoney, Patrick
Abstract: Objective: Using social cognitive theory as a framework, this study examined electronic nicotine delivery systems (ENDS) use, related cognitions, and context among college students. Participants: Respondents were 1229 students attending a mid-sized, northeastern university. Methods: A cross-sectional survey was administered and SPSS was used for analysis. Results: Almost 41% of respondents reported ENDS use in the prior month (past-month user), 26.8% reported trying ENDS but no use in the prior month (occasional user), and 32.3% reported never trying ENDS. The results highlight significant associations in past-month versus occasional use and reasons for initation, location for ENDS use, perceived norms for ENDS use, and outcome expectations for ENDS use. Conclusions: This study highlights a need for theory-based, multi-level strategies to reduce ENDS use. Interventions should increase awareness about the risks of ENDS, include peer-based interventions to foster health-promoting campus social environments, and explore the use of policies restricting campus ENDS use.